Pengaruh Presepsi dan Efektifitas Pembelajaran LMS Terhadap Hasil Belajar Mahasiswa Melalui Motivasi Belajar - Rizeki Dyahmeirina; Yohanes Suhari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze how student perceptions and the effectiveness of the use of a Learning Management System (LMS) influence learning outcomes, with learning motivation as a mediating variable. The approach used was quantitative with an explanatory method. The study involved 125 students of the Accounting Study Program in Semarang City who were selected using a purposive sampling technique. Data collection was carried out through a structured questionnaire using a five-point Likert scale, then the data were processed with validity tests, reliability tests, classical assumption tests, path analysis, and mediation tests with the Sobel test using SPSS version 25.0. The results of the analysis showed that both student perceptions and LMS effectiveness had a positive and significant effect on learning motivation. Meanwhile, student perceptions were not found to have a significant effect on learning outcomes, while LMS effectiveness was shown to have a positive and significant effect. Furthermore, learning motivation played a role as a significant mediating variable in the relationship between perceptions and LMS effectiveness with student learning outcomes. Overall, the results of the study indicate that positive student perceptions of LMS and LMS effectiveness in learning can increase learning motivation, which ultimately can support the achievement of better learning outcomes.